DISTRIBUTION PATTERNS AND SETTLEMENT DENSITY USING NEAREST NEIGHBOR ANALYSIS AND KERNEL DENSITY ANALYSIS IN DIY COASTAL AREAS (JURNAL GEOGRAFI, 2022)
DIY's coastal area is one of DIY's development priorities by establishing the site as an economic corridor that impacts physical development, such as settlements in the coastal area of DIY. This study aims to analyze the distribution and density of settlements. The method used in research is a quantitative descriptive and Geography Information System approach. The analysis used in this study is Nearest Neighbour Analysis (NNA) and Kernel Density Analysis with an analysis tool in ArcGIS 10.5. The results of the NNA show that the three districts located on the coast of DIY have the same distribution pattern characteristics, namely, the clustered pattern, which means the NNA index value is